CHANGE IN BALANCE BETWEEN ACTIVITY OF LIPID PEROXIDATION, ANTIOXIDANT SYSTEM AND FERRUM CONTENT IN RATS WITH EXPERIMENTAL MYOCARDIAL INFARCTION - L. D. Hidirova (Рациональная фармакотерапия в кардиологии)
Aim. To study the balance between activity of lipid peroxidation, antioxidant system and ferrum content in blood, lymph and myocardium of rats with experimental myocardial infarction (EMI).Material and methods. Experimental study included 116 Wistar male rats (200-220 g of body mass). The EMI was caused by subcutaneous adrenaline injection (0.2 mg/100 g of body mass). The EMI was confirmed by electrocardiography and histopathologic data. The plasma/lymph ferrum index was calculated as blood/lymph ferrum content ratio. The neutrophil chemiluminescence analysis was also performed. Intensity of lipid peroxidation was evaluated by levels of malonic dialdealdehyde, the diene conjugates and diketones. The catalase activity and recovered glutathione was assessed in the erythrocyte hemolysate. Activity of superoxide dismutase was determined in serum; total blood antioxidant activity was assessed by chemoluminescent method.Results. The neutrophil activity and lipid peroxidation intensity was increased. The total blood antioxidant activity was reduced (in 2.5-5 times) as well as catalase activity and recovered glutathione level.Conclusion. The balance disorders between lipid peroxidation and antioxidant activity can result in myocardial injury. The ferrum redistribution from serum to lymph is observed in clinical course of myocardial infarction.